Foundation of vortex gravitation, cosmology and cosmogony (Global Journal of Science Frontier Research, 1969)
A hypothesis is proposed concerning the cause of the origin of universal gravitation. This cause consists in a system of the ether vortex rotations. Physical and mathematical grounds are described and the formula for the determination of the space gravitation forces is deduced. On the basis of the vortex gravitation, the principles of creation and existence of the celestial bodies are shown. Methods of the use of the vortex gravitation properties for the space flight projection are proposed.
Keywords: Ether Theory; Vortex Gravitation; Cosmology and Cosmogony